Yup’ik Loanword Etymologies for the Yukaghir Languages and Dialects - Piispanen, Peter (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2022)
In this paper, up to twenty-eight new Yukaghir etymologies are described as Eskimo borrowings into the Yukaghir languages and dialects of far northeastern Siberia, with phonological and semantic considerations for each suggestion. These findings provide new insights into the historical phonology of these ancient borrowings as well as fairly clear etymologies for a number of isolated Yukaghir words. The chronology of the borrowings is also considered, and various factors reveal two different competing hypotheses: the Yukaghir correspondences have either resulted from chronologically different borrowing layers through the ages, or the correspondences actually represent the remnants of an ancient genetic language affiliation between the two, a hypothesis supported by the very divergent phonological shapes and semantics of the correspondences. It is argued that the Eskimo correspondences are invariably of the Yup’ik variety (instead of the Inuit variety), and that Yup’ik language(s) were spoken in much earlier times around the Kolyma River, where Yukaghir is still spoken, and in particular close to the Tundra Yukaghirs. The semantic categorization of the borrowings places most of them as elementary phenomena, actions, and perceptions, and if not actually describing an actual genetic language relationship, this at least suggests very intense linguistic contacts between Yup’ik and Yukaghir under bi- or multi-lingual conditions, such as through tribal marriages and where code-switching was the norm for generations.